A study on problems, roles and factors affecting perceived effectiveness of course leader performance - Juhdi, Nurita; Ahmad, Siti Nor Bayaah; Saad, Hanita Sarah (CERT Publications Sdn. Bhd, 2008)
The present study examined problems faced by course leaders at three different stages (planning, during semester and post semester), their perceptions on their course leader roles and investigated their perceived role effectiveness in leading and managing courses as part and parcel of their role as lecturers. Fifty nine course leaders were involved and results show that common problems faced are in finding the right assignments, time constraint, getting feedback from tutors and monitoring course evaluation in all the regional centers. Results also suggested that course leaders who have the prerequisite skills and knowledge as course leaders and perceived as having high amount of autonomy in their jobs tend to perceive their role performance as effective. Skills and knowledge cited to be principally essential in relation to this study includes expertise in the subject matter, communication skills, interpersonal skills as well as adequate technical skills and know how to be able to cope with the changing landscape of the technologically and computer laden education world.